Prognostic factors for incomplete response in thyroid microcarcinoma: an analysis of initial response to therapy in 517 patients - Faro, Fernanda Nascimento; Simões, Vivian Roberta Ferreira; Ricardo, Gustavo Piech; Cabral, Cristal Peters; Ribeiro, Karina de Cássia Braga; Scalissi, Nilza Maria; Cury, Adriano Namo; Marone, Marília Martins; Padovani, Rosália do Prado; Ferraz, Carolina (Archives of Endocrinology and Metabolism, 2021)
Although thyroid microcarcinoma (TMC) usually has a favorable prognosis, some patients present a higher risk of disease recurrence or persistence. Thus, we aimed at identifying possible risk factors associated with an incomplete response to therapy in TMC. This was a retrospective study of 517 patients with TMC treated with total thyroidectomy, with or without radioactive iodine (RAI) therapy, reclassified after 1.1 ± 0.4 years according to the response to treatment into "favourable" (excellent/indeterminate) or "unfavorable" (biochemical/structural incomplete) responses. We evaluated participants' age, sex, tumor size, histological variants, multifocality, presence of vascular/lymphatic/perineural invasion, extrathyroidal extension, metastatic lymph nodes (LN), and distant metastasis. The effect of RAI therapy on the response range was analyzed in a given subgroup. The mean age observed was 46.4 ± 12.0 years, and 89.7% were female. We noted 97.5% with papillary carcinoma, 27.8% with multifocality and 11.2% with LN metastasis. Although the majority of patients had a low risk of recurrence/persistence (78%), 75% were submitted to RAI therapy. Incomplete response (20.7%) was associated with multifocality (p=0.041; OR=1.619) and metastatic LN (p=0.041; OR=1.868). These variables were strongly correlated (p=0.000; OR=3.283). No cut-off of tumor size was identified as a predictor of incomplete response by the receiver operating curve analysis. RAI treatment did not influence the response of patients with multifocality or LN metastasis. Multifocality and LN metastasis are independent risk factors for incomplete response in TMC patients and are strongly correlated. Additional RAI therapy was not associated with a more favorable response in these subgroups.